AGRICULTURAL PRODUCTION IN CHERNIGIV REGION: CURRENT CHALLENGES AND WAYS TO IMPROVE EFFICIENCY - DVORNYK, Inna; STADNYK, Viktoriya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Agriculture in Chernihiv region traditionally plays a leading role in the economy of the region and the formation of food security in Ukraine. Due to natural and climatic conditions, the region has significant potential for the development of crop and livestock farming, in particular in the production of grain, industrial, vegetable and fruit and vegetable crops, as well as dairy and meat products. However, modern socio-economic and political challenges require new approaches to the organization of agricultural production, technological modernization and increasing its competitiveness. Over the past decade, there has been a decrease in the livestock population, a reduction in dairy farming and a decrease in the share of products produced by households. At the same time, the business sector demonstrates greater adaptability and growth, especially in the production of grain and industrial crops, which have become dominant in the structure of agricultural production. Changes after 2022 are especially noticeable: military operations, loss of land, logistical problems and high cost of production led to a sharp decline in production. However, already in 2023–2024, certain segments demonstrated recovery trends, particularly in large and medium-sized enterprises. The scientific interest is to determine the factors that influence the volume of agricultural production. Internal factors include the technical level of equipment, personnel qualifications, organization of production processes and management structure. External factors are political and economic environment, state regulation, infrastructure provision, competitive pressure. Analysis of recent research by domestic scientists shows that despite the significant achievements in the development of the agricultural sector of Ukraine, a comprehensive study of agricultural production in Chernihiv region, as a border region, requires further attention. The purpose of the work is to analyze the current state of agricultural production in the region, identify problems and challenges, and determine ways to increase the efficiency of the industry. The practical significance of the study is to formulate recommendations for the modernization of technologies, optimization of the production structure, development of livestock farming and the introduction of innovations, which will ensure the competitiveness of the agricultural sector of the region and enhance its contribution to the food security of the state.